IMPACT OF FDI IN ORGANISED RETAILING IN MALAYSIA: STUDY OF DIFFERENT INTERMEDIARIES - Batra, Gurdip S.; Anand, Tamana (Poslovna ekonomija, 2017)
This study examines the impact of FDI in organised retailing in India with reference to consumers and retailers. Findings reveal that consumers are aware of economic, social, technological benefits of FDI. Foreign direct investment in organised retailing for food n grocery and apparel n clothing is related with product & store attributes, economic, social, technological benefits. Retailers should focus on marketing strategies such as loyalty programmes, free gifts, store image and festival offers to attract customers as compare to organised retailers. There will be increase in jobs and increase in standard of living if foreign retailers increase their business in India. Foreign retailers can help small traditional retailers by trainings, new market opportunities, quality assurance, technology support, contract farming, efficient marketing chain, better packaging and e-commerce. There can be some problems to be faced by retailers like late payment and difficulty in consistent supply but these issues can be addressed by the Government.